Tag clouds for situated interaction and place profiling - José, Rui (2011)
Tag clouds have become very popular as visual representations of the main topics in document sets or as navigation tools that can provide quick access to resources related with specific topics. However, their ability to represent the information environment associated with any meaningful reality in a way that is collectively visible, actionable and easily understood may also be very relevant, even when the reality being represented is no longer a set of documents or resources, but a stream of interactions occurring within a particular ubiquitous computing environment. In this paper, we explore the use of tag clouds within the context of situated displays and services. We hypothesise that such tag clouds may have a role as dynamic representations of place and also as interaction controls, supporting the same comprehension and navigation functions of classical tag clouds. We describe two case studies in which this concept of situated tag cloud has been experimented in real-world settings. The case studies demonstrate two different applications of the tag cloud concept as the basis for place description and situated interaction. The results obtained from the case studies suggest that situated tag clouds can indeed provide valuable representations of place and situations and can also support simple interaction models, allowing people to reason about the system behaviour and how it is being influenced by new interactions.